Application Of Problem Based Learning (PBL) Model To Improve Student Learning Outcomes On Acid Base Titration Material For Class XI SMA Negeri 5 Palu - Rahma, Dina; Jura, Minarni Rama; Ningsih, Purnama (Media Eksakta, 2025)
The goal of this study was to describe how the Problem Based Learning approach improved students’ learning outcomes on acid-base titration material in class XI SMA Negeri 5 Palu. Simple Random Sampling was used to sample the sample for this study, which consisted of two classes, class XI MIPA 2 as replication class I (31 students) and class XI MIPA 4 as replication class II (30 students). The N-gain test was used to assess the research data from the two classes. The average N-gain value of 0.79 was included in the high category for replication class I, and the average N-gain value of 0.73 was included in the high category for replication class II. According to the data analysis, the average pretest and posttest values for replication class I were 25.32 and 84.52, respectively, with a 59.2 increase in learning outcomes. While replication class II were 28 and 81, respectively, with a 53 increase in learning outcomes. As a result, it can be concluded that using the Problem Based Learning model in class XI MIPA on acid-base titration material at SMA Negeri 5 Palu can inmpove student learning outcomes.